2006
DOI: 10.1103/physrevb.74.220504
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium transport in superconductor/ferromagnet/superconductor diffusive junctions: Interplay between proximity effect and ferromagnetism

Abstract: The theory of the I-V characteristics in diffusive superconductor/weak ferromagnet/superconductor (SFS) junction is developed. We show that the exchange field h of the ferromagnet manifests itself as an additional conductance peak at eV ∼ ∆ + h in the phase-coherent regime, when the Thouless energy is of the order of superconducting order parameter. The excess current exhibits non-monotonous dependence on the exchange field and non-trivial temperature behavior, which is strongly influenced by the temperature d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…85 To some extent, from the mathematical point of view, the voltage V is analogous to the exchange field h. The form of the I -V curve for an S/F/S Josephson contact has been found in Ref. 86.…”
Section: A Josephson Current In S M /Fl/n/fl/s M Junctionsmentioning
confidence: 99%
“…85 To some extent, from the mathematical point of view, the voltage V is analogous to the exchange field h. The form of the I -V curve for an S/F/S Josephson contact has been found in Ref. 86.…”
Section: A Josephson Current In S M /Fl/n/fl/s M Junctionsmentioning
confidence: 99%
“…In the anti-ferromagnetic alignment of the magnetizations of the F layers a strong suppression of superconductivity was found, leading to a large magnetoresistive effect. In Josephson junctions the effect of spin injection 27 and presence of weak ferromagnets 28 was considered, while the effect of Andreev reflection on spin accumulation in a ferromagnetic wire was reported in Ref. 29.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of ac current spin polarization, calculated according to Eq. (17), is represented in inserts to Figs. 3(a) and 3(b) at x = d/2 and x = 0, respectively.…”
mentioning
confidence: 99%
“…In particular, it was shown that by tunnel coupling of the normal regions of two superconductor-normal metal-ferromagnet trilayers the absolute spin-valve effect can be realized for a certain interval of voltages applied between the normal regions 16 . For voltage-biased superconductor-weak ferromagnet-superconductor Josephson junction the interplay between the proximity effect and the Zeeman exchange field results in additional peak-like features in the I-V characteristics 17 . The ac Josephson current in superconductor-ferromagnet-superconductor voltage biased junction was also studied 18 .…”
mentioning
confidence: 99%